Problems and Obstacles of People Who Cycling in Hatyai City Municipality and Khohong Town Municipality, Songkhla Province - Ruthirako, Poonyanuch (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2018)
The research aimed to study the problems and obstacles of people who cycling in Hatyai City Municipality and Khohong Town Municipality, Hatyai District, Songkla Province. The samples of 400 population were selected by convenience sampling method. A questionnaire was used as a research instrument and t-test and F-test were utilized to analyze the data. The results showed that most of people are do not cycling in daily life (67.5 percents). There are only 32.5 percent do cycling and the objective of cycling is for exercise (24.8 percent). The frequency of cycling are 1-2 days per week (13.8 percent). The cycling distance is about 1.1-3.0 km (9.8 percent) and time of cycling is 15-30 minutes (11.3 percent). The top three problems and obstacles that affected the people to cycling in Hatyai City Municipality and Khohong Town Municipality are feeling unsafety, no bike lane, and no bicycle parking area. But the least problems and obstacles is the feeling of being looked down as poor people.